Computational design based approaches for public space resilient regeneration - Losasso, Mario; Leone, Mattia; Tersigni, Enza (TECHNE - Journal of Technology for Architecture and Environment, 2020)
In urban areas, the issue of resilient-based design for adaptation to climate impacts is one of those where the interdependence between technological innovation, resource governance and sustainable development strategies is relevant. Public spaces are a key system for testing the most effective strategies for reducing climate impacts through approaches that use computational design tools in climate adaptation actions. The paper presents the results of the Athenaeum Research Project funded for 2017-2019 by Federico II University entitled SIMMCITIES_NA, Scenario Impact Modelling Methodology for a Climate change-Induced hazards Tool for Integrated End-users Strategic planning and design - Napoli.